Chronic pain in pachyonychia congenita: evidence for neuropathic origin. (25th April 2018) - Brill, S.; Sprecher, E.; Smith, F.J.D.; Geva, N.; Gruener, H.; Nahman‐Averbuch, H.; Defrin, R.
Summary: Background: Pachyonychia congenita (PC) is a rare autosomal dominant skin disease, with chronic pain being the most prominent complaint. Histological studies showing alterations in sensory innervation, along with reports on alterations in mechanical sensitivity, suggest that PC may be a form of neuropathy. Objectives: Here, for the first time, we aim to evaluate systematically the sensory function of patients with PC vs. controls, in order to investigate the pathophysiology of PC. Methods: Patients ( n = 62) and controls ( n = 45) completed the McGill and Douleur Neuropathique‐4 (DN4) questionnaires. Sensory testing included detection and pain thresholds, pathological sensations, conditioned pain modulation (CPM) and temporal summation of pain. Results: A moderate‐to‐severe chronic pain in the feet, throbbing and stabbing in quality, was highly prevalent among patients with PC (86%) and was especially debilitating during weight bearing. In addition, the majority of patients had a DN4 score ≥ 4 (62%), static allodynia (55%) and tingling (53%) in the feet. Compared with controls, patients with PC exhibited thermal and mechanical hypoaesthesia and mechanical hyperalgesia in the feet. CPM was reduced among the patients, and was associated with more enhanced mechanical hyperalgesia in the feet. The specific gene and nature of the causative mutation did not affect any of these features. Conclusions: Although thermal and mechanical hypoaesthesia may result from thicker skin, its presentation in painful regions, along with mechanical hyperalgesia and allodynia, point towards the possibility of neuropathic changes occurring in PC. The clinical features and DN4 scores support this possibility and therefore neuropathic pain medications may be beneficial for patients with PC. Abstract : What's already known about this topic? Chronic pain is the most prominent and debilitating complaint in pachyonychia congenita (PC). The origin of this pain has not been established and hence an appropriate intervention is also lacking. Histological studies have found alterations in sensory innervation. What does this study add? Systemic sensory testing revealed hypoaesthesia along with mechanical hyperalgesia and allodynia (pain resulting from a nonpainful stimulus) in the painful body regions. Causative mutation and gene harbouring did not affect any of these features. The clinical and physiological characteristics of the pain suggest a possible neuropathic origin. Neuropathic pain medications may be beneficial for patients with PC. Linked Comment: Krupiczojc and O'Toole. Br J Dermatol 2018; 179 :11–12 . Respond to this article